2014
DOI: 10.1259/dmfr.20140019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metal artefact reduction around dental titanium implants in cone beam CT

Abstract: The MAR tool in the software of the ORTHOPANTOMOGRAPH OP300 CBCT scanner does not significantly correct the voxel gray values affected by the metal artefact in the vicinity of an implant in human dry mandibles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…; Parsa et al. ). An underestimation of bone defects around implants by approximately 1 mm was documented for CBCT analysis when compared to the histological situation in a mini‐pig model (Corpas Ldos et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Parsa et al. ). An underestimation of bone defects around implants by approximately 1 mm was documented for CBCT analysis when compared to the histological situation in a mini‐pig model (Corpas Ldos et al.…”
Section: Discussionmentioning
confidence: 97%
“…Physiological bone structures can cause significant radiation scattering, which cannot be assessed in studies using homogeneous phantoms. 23 Parsa et al 23 also calculated mean greyscale values to assess AR use in sites adjacent to dental implants. By comparing the areas of interest before and after implant insertion, they reported a significant increase in mean greyscale values after surgery and, when comparing the images obtained with and without the use of the AR, found out that there was no change in greyscale values with the tool activated.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have evaluated this tool, and the results are inconclusive as to its influence on the final image quality. [21][22][23] When evaluated for root fracture diagnosis in teeth filled with gutta-percha, the use of an AR led to decreased diagnostic sensitivity and specificity. 4 Additionally, no differences were observed in the detection of simulated periodontal and peri-implant vestibular defects with or without the use of an AR.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms within 3D imaging software were developed to reduce metal generated artefacts. One in vitro study found that an artefact reduction algorithm does not significantly correct the altered grey values in the vicinity of implants (Parsa et al 2014). Another study investigated the accuracy of CBCT images obtained with and without the use of artefact reduction modes in detecting simulated peri-implant defects (Kamburoglu et al 2013).…”
Section: Assessment Of Bone and Soft Tissuementioning
confidence: 99%